Methods Of Teaching English Terminology in Higher Education - Mustaeva Guldora Salaxiddinovna (Genius Journals, 2021)
Higher education instruction in English in non-English speaking countries has become a reality in several countries and contexts. The policy towards the adoption of English as language of medium of instruction (EMI) has led to a situation in which students are faced with the need of coping with learning new content in a language different from their mother tongue and teaching staff needs to deliver their courses in English, which is not their first language in many cases. The present review article focuses on the studies concerning EMI in higher education, reporting on didactical strategies employed by the teaching staff and students to cope with the learning context.
Keywords: Higher Education; English; English as medium of instruction